The diversity of key anabolic genes in antarctic hypolithons - Makhalanyane, Thulani Peter (2014)
>Magister Scientiae - MSc === Antarctica is known for its pristine environments. A variety of unsuitable environmental conditions were once thought to render the continent unsuitable for sustaining life. However, metagenomic data have revealed a wealth of species diversity in a range of biotopes.Hypolithons, photosynthetic communities which live under translucent rocks in climatically extreme environments, are an important input source for both carbon (C) and nitrogen (N) in this hyperarid desert environment. Microbial contribution to biogeochemical cycling resulting in fixation of both C and N remains poorly understood. Moreover, there is a reported close interplay between both cycles, with nitrogen being reported to be a limiting factor in carbon assimilation.In this study the diversity of C and N fixing organisms was investigated by using the cbbL and nifH genes as phylogenetic and functional markers. High Molecular weight metagenomic DNA and RNA was extracted from hypolithons. PCR amplification was carried out using cbbL (800 bp for red-like, 1,100 bp for green-like) and nifH (360 bp) gene specific primers.Resultant PCR products were used to construct libraries which were screened for correct sized inserts. Restriction Fragment Length Polymorphism (RFLP) was used to de-replicate clones prior to sequencing. Phylogenetic positions from both clone libraries were established by aligning nucleotide sequences and constructing similarity trees using NJ clustering methods.BLASTn results indicated the presence of previously uncultured organisms which contain cbbL and nifH genes. BLASTn results were characterized by low percentages of maximum identity (typically <95%), a potential indicator of novel taxa. Sequences from respective libraries clustered with cyanobacteria such as Nostoc, Scytonema, and Tolypothrix and α-, β-, and γ-Proteobacteria such as Azotobacter, Agrobacterium and Mesorhizobium. Generally sequence results indicate a largely homogenous, being dominated by specific taxa. Each group may contain potential keystone species, essential for both biogeochemical cycling in oligotrophic environment.